Hazlo como hombre (Do it like an hombre) [videorecording (DVD)] - López, Nicolás, 1983-; Ochmann, Mauricio, 1977-; Busto, Humberto, 1978-; Dosal, Alfonso (Lionsgate, 2018)
Raul, Eduardo and Santiago have led a happy and masculine life from their childhood, until one day, Santiago confesses to them that he is gay. Raul, the alpha male and more homophobic of the three, will try to convince his friend that his is nothing more than a simple sexual confusion, until, when the situation becomes unsustainable, Eduardo and Raul will leave aside their prejudices and decide to help Santiago to venture into his new gay life.